Incentives for private innovations – is public support necessary? - Lewczuk, Anna; Lewkowicz, Jacek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Do firms really need public support in order to offer product and process innovations? Recent articles and professional reports reflect the importance of public support for private innovations. The issue is actual and relevant both from scientific and practical points of view. Public support for actions aimed at developing crucial innovations is an example of creating institutional incentives for the desired behaviour of firms. The question of public support for innovations is critical for ongoing national and international policies in raising the innovativeness of economies. The main goal of the paper is to review the idea of public support for innovativeness and to verify its effects in European countries empirically, by using simple probit and bivariate probit models. This paper aims to provide a systematic analysis of the problem from an institutional perspective. The results of the analysis contribute to a better understanding of the nature of public spending on private innovations and the outcome of such innovation policies. It is also an added value to the discussion over actual public policies which has been so far inconclusive
Argumenta Oeconomica, 2020, Nr 2 (45), s. 105-139
Keywords: innovation policy; public support; public policy; institutional economics